ABVD Without Radiation for Newly Diagnosed Pediatric and Young Adult Patients With Hodgkin Lymphoma: A Single Center Retrospective Analysis of 28 Consecutive Patients. Issue 4 (May 2018) - Stieglitz, Elliot; Dinh, Tu; Phelps, Andrew S.; Pampaloni, Miguel H.; Olshen, Adam B.; Robbins, Elizabeth
Abstract : Hodgkin lymphoma (HL) is the most common malignancy affecting adolescents and young adults. Treatment with a combination of chemotherapy and radiation results in cure rates of >90%. However, radiation therapy causes significant late effects and avoiding radiation entirely for patients who respond to chemotherapy is an accepted strategy. Since 2011, 28 consecutive patients diagnosed with classic HL have been treated with doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD) for 4 to 6 cycles. Patients who achieved a complete metabolic response (CMR) as assessed by [ 18 F] fluorodeoxyglucose positron emission tomography by the end of chemotherapy did not receive radiation. Among the 27 evaluable patients, 26/27 (96.2%) achieved a CMR with ABVD alone with 24/27 (88.9%) having achieved a CMR after 2 cycles. Event-free survival at 5 years is 90.5% and overall survival is 100% with a median follow-up time of 22.4 and 22.1 months, respectively. Treating pediatric and young adult HL patients with ABVD alone results in CMRs in >95% of patients. Patients who were refractory to ABVD or relapsed after treatment eventually achieved remission with a combination of standard and novel salvage therapies. This regimen demonstrates the feasibility of avoiding upfront radiation in newly diagnosed pediatric HL patients. Abstract : Supplemental Digital Content is available in the text.